Sustainable Acoustic Performance: Implementing PFAS-Free Membranes in Consumer Electronics Microphones - Sugirtha Krishnamurthy, (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article examines the transition from PFAS-based to PFAS-free membrane technologies in consumer electronics microphones, focusing on environmental sustainability and performance optimization. The article analyzes the technical challenges, material alternatives, and implementation strategies while evaluating the economic implications of this transition. Through comprehensive testing and analysis, the article demonstrates that PFAS-free alternatives can achieve comparable performance metrics while significantly reducing environmental impact. The article also explores manufacturing integration challenges, quality assurance protocols, and future directions in sustainable acoustic materials development, providing a framework for industry-wide adoption of environmentally responsible practices.
Keywords: PFAS-free membranes; Sustainable acoustics; Environmental compliance; Biodegradable polymers; Manufacturing optimization